User Experiences from L2 Children Using a Speech Learning Application: Implications for Developing Speech Training Applications for Children. (1st November 2018) - Uther, Maria; Smolander, Anna-Riikka; Junttila, Katja; Kurimo, Mikko; Karhila, Reima; Enarvi, Seppo; Ylinen, Sari
Abstract : We investigated user experiences from 117 Finnish children aged between 8 and 12 years in a trial of an English language learning programme that used automatic speech recognition (ASR). We used measures that encompassed both affective reactions and questions tapping into the children' sense of pedagogical utility. We also tested their perception of sound quality and compared reactions of game and nongame-based versions of the application. Results showed that children expressed higher affective ratings for the game compared to nongame version of the application. Children also expressed a preference to play with a friend compared to playing alone or playing within a group. They found that assessment of their speech is useful although they did not necessarily enjoy hearing their own voices. The results are discussed in terms of the implications for user interface (UI) design in speech learning applications for children.